Agricultural input subsidies: the recent Malawi experience - Chirwa, Ephraim (Oxford University Press, 2013)
This title provides a detailed, comprehensive, and objective analysis of Malawi's agricultural input subsidy programme, its history, implementation, achievements, and shortcomings.